Social networking in nonprofit organizations: the case of Amnesty International Portugal - Galelo, João (2017)
In a world in which the information is spread faster than ever, natural disasters, atrocities on fundamental human rights or even on the sustainability of our planet occupy a big part of our daily lives whether they occur next to us or not. NGOs thus have an overriding role, following their ideals and motivating people to joining them on their campaigns. That is however the same world in which the term “crisis” has come to stay, in which the competition became global, and in which the credibility towards business has reached historical lows. Is then urgent for NGOs to understand this framework, using all new tools available in order to remain relevant, reliable, and efficient. Marketing and its new trends can (and must) intercede here. Nonprofit business requires specific marketing strategies with their unique characteristics, making social business a distinct science that is often misinterpreted. This research aims to sensitize to the use of appropriate marketing practices in NGOs, providing guiding lines through social marketing practices and embracing new trends in marketing, concretizing in practical notes with the collaboration of the Portuguese section of Amnesty International.